Respuesta :
Answer:
a(66) = -1133
Step-by-step explanation:
The common difference here is -17. Note that -45 is equal to the previous value (-28), and that subtracting 17 from -28 yields -45.
Then the explicit equation of this arithmetic sequence is
a(n) = -28 - 17(n - 1)
and the 66th term is a(66) = -28 - 17(65), or a(66) = -1133
Answer:-1133
Step-by-step explanation:
-28,-45,-62
First term=a=-28
Common difference=d=-45-(-28)
d=-45+28
d=-17
Using the formula
Tn=a + d x (n-1)
T66 is the 66th term
T66=-28 + (-17)(66 - 1)
T66=-28 + (-17)(65)
T66=-28 - 1105
T66=-1133
66th term=-1133